2015
DOI: 10.1016/j.neuron.2015.09.019
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Representation of Sequences: From Transition Probabilities to Algebraic Patterns and Linguistic Trees

Abstract: A sequence of images, sounds, or words can be stored at several levels of detail, from specific items and their timing to abstract structure. We propose a taxonomy of five distinct cerebral mechanisms for sequence coding: transitions and timing knowledge, chunking, ordinal knowledge, algebraic patterns, and nested tree structures. In each case, we review the available experimental paradigms and list the behavioral and neural signatures of the systems involved. Tree structures require a specific recursive neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
458
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(478 citation statements)
references
References 161 publications
(214 reference statements)
18
458
1
1
Order By: Relevance
“…If everything goes well, this path would end successfully with arrival at the dinner party. Note that not only is there a deep generative model in relation to time in play here (Dehaene et al, 2015), there is also a hierarchical depth in terms of short and long-term policies, i.e., trajectories of states (see Friston et al, 2017c).…”
Section: Affordances and Policiesmentioning
confidence: 99%
“…If everything goes well, this path would end successfully with arrival at the dinner party. Note that not only is there a deep generative model in relation to time in play here (Dehaene et al, 2015), there is also a hierarchical depth in terms of short and long-term policies, i.e., trajectories of states (see Friston et al, 2017c).…”
Section: Affordances and Policiesmentioning
confidence: 99%
“…But this is business as usual when trying to trace the linguistic functions of the brain at that level of analysis (Poeppel & Embick 2005), as it exemplarily also happens with the system of computation that endows languages with Chomsky's Basic Property (Dehaene et al 2015). Notwithstanding, the representational/computational approach historically endorsed by Chomskyan linguistics seems apt to provide an abstract perspective (Chomsky 1980) from which to begin securing some relevant preliminary conclusions that, paradoxically enough, put seriously into question Chomsky's extreme internalism.…”
Section: Redefining Boundaries: Enter Hybridsmentioning
confidence: 99%
“…In many regions of the world, including North America, numbers increase in magnitude from left to right and text is read from left to right (Shaki, Fischer, & Petrusic, 2009). Indeed, many studies have shown that people respond faster with the left hand when presented with small numbers, and faster with the right hand when presented with larger numbers (i.e., the SNARC effect; Campbell & Scheepers, 2015;Dehaene, Bossini, & Giraux, 1993;Dehaene, Meyniel, Wacongne, Wang, & Pallier, 2015;see Wood, Willmes, Nuerk, & Fischer, 2008, for a meta-analysis). This correspondence generalizes to other ordinal sequences, such as months and letters (Gevers, Reynvoet, & Fias, 2003), suggesting that in many contexts, Bright is more.^Moreover, people tend to demonstrate an orthogonal association in various spatial tasks, simultaneously mapping left to low and right to high (i.e., the SRC effect; see Cho & Proctor, 2003, for a review).…”
Section: Crossmodal Pitch Correspondencesmentioning
confidence: 99%
“…Horizontal size estimates might reflect semantic or numeric coding. For example, large numbers are associated with rightward responses in various cognitive tasks (Campbell & Scheepers, 2015;Dehaene et al, 1993;Dehaene et al, 2015;Shaki et al, 2009;Wood et al, 2008). However, the interactions between head elevation (standing or sitting) and voice pitch manipulation observed in Experiment 2 suggest that our findings are not the result of simple numeric-size mapping.…”
Section: Interpretation and Implicationsmentioning
confidence: 99%